The Relationship Between Work Stress and Locomotive Maintenance Officer Performance - Setyo Darmawan, Endras; Churniawan, Erifendi; Ayudha Arkadanita, Denta (Riviera Publishing, 2023)
Limited human resources and time demands can increase workload resulting in faster work stress. If handled over time, it will have an impact on the performance of officers and can also increase work stress. Therefore, this study aims to determine the relationship between work stress and the performance of locomotive maintenance workers at the Purwokerto Locomotive Depot. This study uses a type of quantitative research. Data collection methods used in this research are primary and secondary data sources. The data analysis technique used is the instrument test, Spearman rank correlation and Spearman rank hypothesis test. Calculate the rho count on the work stress variable with a performance showing a value of 0.479, while for the comparison results, the value of the rho table shows several 0.439. In the hypothesis decision-making criteria that rho count > rho table 0.479 > 0.439, there is a relationship between work stress and employee performance which can also be seen from sig. (2-tailed) of 0.028. Based on retrieval, if the sig. (2-tailed) 0.028 <0.05 means that there is a significant relationship between work stress and performance variables. Spearman's rank hypothesis test found a relationship with a correlation value of -0.479, meaning that the relationship is vital in the moderate category. The direction of the relationship from this study is harmful or not unidirectional. And the rho count is greater than the rho table, which is 0.479, which is greater than 0.439, so the hypothesis shows a relationship between work stress and employee performance.